Geragogika resocjalizacyjna w jednostkach penitencjarnych. Starość, długowieczność więzienna - Toroń-Fórmanek , Barbara (Studia Edukacyjne, 2018)
For a human being deprived of freedom, prison isolation can be a source of frustration. However, the needs of the elderly due to specific conditioning connected with the aging process make their adaptation to prison conditions more complicated. The article concerns specific problems of seniors in custody in penitentiary units with reference to theoretical and practical aspects of pedagogy of senescence and resocialization geragogy. The main subject of interest of pedagogy of senescence is upbringing of an elderly person, understood as supporting their development (physical, mental, social, cultural, spiritual). Resocialization geragogy draws attention to the need to allow for psychophysical conditions of seniors, reinforcing their sense of dignity and relevance of subjecting them to supportive influence aiming at growing their awareness that senility is a good time to acquire knowledge, skills and create habits, attitudes and behaviors.